(untitled) (Medico Legal Update, 2020)
Objective: This study aimed to determine the impact of smartphone use in head posture and functional ability of upper extremity in adolescents and the correlation between them. Design: Cross sectional design. Method: Forty adolescents divided into two groups (group I and group II) based on the smartphone time use per day. They were assessed for neck pain by Visual analogue scale (VAS), the disability of the upper extremity by Upper Extremity Functional Index (UEFI) and the head posture angles by AutoCAD photographic analysis. Results: The results of this study represented significant differences in all measurable variablesinthe group (II) as compared to the group (I). Also, the results of this study represent there were significant strong relationships between the measurable variables. Conclusion: We could conclude that the prolonged duration of smartphone use had significant effects on the head posture and functional ability of adolescents.